The Im/possible Femininity of Nina Arsenault: theatrical gender in I w@s B*rbie and The Silicone Diaries - Low, Stephen (Revista Brasileira de Estudos da Presença, 2020)
This essay argues that the performed corporeality of performance artist Nina Arsenault demonstrates how gender can be constituted by two mutually exclusive theories of gender simultaneously. Specifically, Arsenault im/possibly embodies gender as performative and as an essential psychic sense of self. Her expression of a feminine identity onstage is incompatible with theories of gender performativity because it incorporates a voluntary act: performance in the theatre. Arsenault also opposes theories that claim gender is an essential psychic sense of self by expressing her sense of self in her art practice/everyday life. Arsenault highlights that the theatrical materiality she embodies, which also further establishes her femininity, is im/possibly performatively constituted. Put simply, Arsenault embodies gender through performance and performativity.